Business-IT Alignment through Enterprise Architecture in a Strategic Alignment Dimension: A Review - Yoppy Mirza, Maulana; Zafril Rizal, M Azmi; Eh Phon, Danakorn Nincarean (Universitas Pesantren Tinggi Darul Ulum (Unipdu), 2023)
Business-IT Alignment (BITA) refers to the fit between business and IT strategy. BITA is important for realizing the achievement of organizational goals, enhancing performance, and gaining competitive advantage in an organization. BITA is a crucial concern for organizations and remains a top topic from the perspective of business executives. BITA can be realized through Enterprise Architecture (EA), which is a comprehensive and holistic instrument for managing and maintaining BITA. However, despite numerous literature studies on the BITA model or framework through EA, the research is currently more focused on technology planning than strategic planning. Meanwhile, strategic planning is the most crucial challenge of the EA framework because it is the embodiment of BITA in the strategic alignment dimension. The current study aims to conduct a literature review of BITA through EA in the strategic alignment dimension. This literature study resulted in 25 out of 100 papers and classified into five strategic alignments. The review identified 25 relevant papers out of 100 and categorized them into five strategic alignments. The study's contributions include solutions in the form of stages for developing strategic alignment through EA based on business strategy models. The five stages are as follows: 1) Identification of vision, mission, and goals; 2) SWOT-based strategy analysis; 3) BSC-based strategy mapping; 4) BPMN-based business process mapping; and 5) Determination of IS/IT. This study's impact on further research is that it can be used as a basis for developing BITA through EA, based on the five stages identified.